Preparation of Natural Hydroxyapatite from Bovine Femur Bones Using Calcination at Various Temperatures - Khoo, W.; Nor, F.; Ardhyananta, H.; Kurniawan, Denni (2015)
© 2015 Calcium phosphate based biomaterials have received great interest since the main constituent of inorganic mineral component in human bone is hydroxyapatite (HAP). This study aims to extract the natural HAP from bovine femur bone at different calcination temperature with different particle size. The experiment starts with cleaning process of fresh bovine femur bones. Then bovine bones were ground into different particle size (x = 45 µm, 45 < x = 63 µm, and 63 < x = 125 µm). All bone samples were furnace heated at temperatures of 700 °C, 900 °C, and 1100 °C for three hours. Obtained apatite was characterized using field emission scanning electron microscope (FESEM), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffraction (XRD). The results indicate that increasing calcination temperature leads to organic free and higher crystallite size of HAP. In terms of particle size, crystallite size is increasing as particle size increases but the increment crystallite size is not significant. The report here proposed that calcination temperature above 700°C may utilize in bone tissue engineering application.